Breeding ecology of Kittlitz's Murrelets on Kodiak Island, Alaska. Issue 4 (16th October 2018) - Lawonn, M. James; Roby, Daniel D.; Piatt, John F.; Pyle, William H.; Corcoran, Robin M.
Abstract: Little is known about the breeding ecology of Kittlitz's Murrelets ( Brachyramphus brevirostris ), a species suspected to have experienced both local and regional population declines in recent years. We studied aspects of their breeding ecology on Kodiak Island, Alaska, to better understand this poorly described member of the family Alcidae. We found 53 nests of Kittlitz's Murrelets during our study (2008–2011) and placed nest cameras at 33 nests to collect data on parental nest attendance, nestling provisioning, and nest survival. Incubation shift exchanges by adults generally occurs either prior to sunrise or after sunset. Adults brooded nestlings for just one day after hatching and did not attend nests thereafter except during provisioning visits. Adults provisioned nestlings an average of 107 times during nestling periods, with a single fish delivered during each visit. Pacific sand lance ( Ammodytes hexapterus ), a high‐lipid forage fish, accounted for 92% of fish delivered to nestlings. Nestlings grew rapidly, with a logistic growth rate constant ( K ) of 0.291, the highest rate yet documented among semiprecocial alcids. Young fledged an average of 25 d after hatching, when their body mass had reached an asymptote of 135.5 g, or 57% of adult body mass. Age at fledging and asymptotic nestling body mass (percent of adult mass) were low compared to other semiprecocial alcids. The mean number of young fledged per nest was 0.093, with 47% of nests predated, and nestlings dying prior to fledging at 21% of nests. The low number of parental provisioning visits, rapid nestling growth rates, and short nestling periods are consistent with adaptations to reduce the likelihood of nest predation and the energy expended by parents. The risk of nest predation and high energetic cost of breeding may make the reproductive success of Kittlitz's Murrelets more sensitive to declines in the availability and quality of their prey than most other alcids.